2015
DOI: 10.1155/2015/520759
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Managing Type 2 Diabetes Mellitus in Greece: A Retrospective Analysis of 10-Year Patient Level Data “The HERCULES Study”

Abstract: Objective. This study aimed to estimate the mean annual cost of treating type 2 diabetes mellitus patients (T2DM) including complications and comorbidities in Greece. Design. A noninterventional retrospective study was based on patient level data analysis (bottom-up approach) from medical records, with at least 10-year-follow-up data. Results. The total annual cost per patient for managing diabetes in Greece was estimated at € 7,111 and was, statistically significantly, higher for patients with inadequate glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
2
20
0
2
Order By: Relevance
“…After accounting for baseline co-morbidities, costs were primarily incurred through inpatient acute hospitalizations, physician visits, prescription medications, and assistive devices [ 5 ]. Similar results have been found in other countries, including the USA and Europe [ 6 11 ].…”
Section: Introductionsupporting
confidence: 90%
“…After accounting for baseline co-morbidities, costs were primarily incurred through inpatient acute hospitalizations, physician visits, prescription medications, and assistive devices [ 5 ]. Similar results have been found in other countries, including the USA and Europe [ 6 11 ].…”
Section: Introductionsupporting
confidence: 90%
“…44% of total costs. This is confirmed by another Greek study which found that management of diabetes related comorbidities accounted for 48% of costs, while pharmaceutical treatment accounted for 35.9% [ 9 ]. The high cost of managing diabetes comorbidities is further illustrated in the international literature.…”
Section: Discussionsupporting
confidence: 65%
“…The American Diabetes Association (ADA) estimated the total cost of diabetes in the US at $174 billion in 2007 [ 8 ]. A recent Greek study estimated the total annual cost per patient for managing T2DM in Greece at €7111 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study from Spain, medications represented 29.7 percent of the total direct costs of managing T2DM (40). In Greece, medications represented 35.9 percent of the total direct costs (41), while in Iran and Colombia, proportions were of 46 percent and 47 percent, respectively. Other Brazilian studies showed medications representing 48 percent (13) and 42 percent (6) of the total direct costs of T2DM.…”
Section: Discussionmentioning
confidence: 99%